Gravity Compensation and Feedback of Ground Reaction Forces for Biped Balance Control - Satoshi Ito; Shingo Nishio; Yuuki Fukumoto; Kojiro Matsushita; Minoru Sasaki (Applied Bionics and Biomechanics)
This paper considers the balance control of a biped robot under a constant external force or on a sloped ground. We have proposed a control method with feedback of the ground reaction forces and have realized adaptive posture changes that ensure the stability of the robot. However, fast responses have not been obtained because effective control is achieved by an integral feedback that accompanies a time delay necessary for error accumulation. To improve this response, here, we introduce gravity compensation in a feedforward manner. The stationary state and its stability are analyzed based on dynamic equations, and the robustness as well as the response is evaluated using computer simulations. Finally, the adaptive behaviors of the robot are confirmed by standing experiments on the slope.